Project: Analysis, Design, and Information System for a Web-Based Library System - Azizah Hanifah; Dira Bulan Dari; Dewangga Nugroho Anwar; Lina Rosalinda; Yudi Setiawan (Indonesian Journal of Computer Science and Engineering, 2026)
The system to be developed is a web-based library system. This system is designed to facilitate library administration in storing information regarding books, library collections, book loans, and collection loans, as well as overall library management. This system was developed to meet the needs of library management, which requires a system capable of improving operational efficiency and providing information on book and library collection loans. In assessing the resulting added value, the system is expected to have a positive impact in line with these needs.The development of this web-based system is also expected to improve the productivity and effectiveness of library services by automating the business processes of library units. On an intangible level, the developed system can enhance the user experience in terms of convenience and satisfaction, as well as increase the value of the library as a provider of educational services to the community.